The landscape of the urban perimeter of the Grajaú river (Maranhão) analyzed from visual quality indicators (Research, Society and Development, 2019)
This paper analyzes the environmental perception and the analysis of the landscape of the urban perimeter of the Grajaú river, in the city of the same name, state of Maranhão – Brazil. The objective was to analyze the environmental perception of grajauense population in relation to changes in the landscape of Grajaú river, as well as the impacts generated by human activities over the past few years. The research was qualitative and the methodology consisted of bibliographical review about the landscape and environmental perception terms in geographical approaches and were used in the indicators visual quality of the landscape, methodological approach adopted from Pires (2005). To check the degree of environmental perception of population were conducted semi-structured interviews. The results showed that the landscape of the Grajaú river presents average visual quality and although the population has sensitivity in relation to the situation of the river, there is little actions for their conservation.